Comparison of anterior tab flap and underlay tympanoplasty techniques in anterior tympanic membrane perforations - Mutlu, Fatih; Durmuş, Kasım; Öztürk, Murat; Değer, Hasan Mervan (Journal of Surgery and Medicine, 2021)
Background/Aim: Closure of anterior tympanic membrane perforation is surgically demanding with high rates of graft failure. The anterior tab flap (ATF) technique is a modification of underlay tympanoplasty which claims higher success rates for repairing anterior and subtotal perforations. Our main aim was to compare graft take rates of ATF and underlay techniques in anterior tympanic membrane perforations. Method: In this retrospective cohort study, 41 patients with anterior tympanic membrane perforations who underwent tympanoplasty at a tertiary referral center were analyzed. The patients were grouped according to the technique used. Demographic, clinical, and follow-up information as well as preoperative and postoperative 6th-month audiometric data were collected and compared between the groups. Results: Four patients were lost to follow-up. Eighteen patients in the ATF arm and 19 patients in the underlay arm were compared. Graft take rates were 94.4% in the ATF group and 73.7% in the underlay group (P=0.180). An air conduction threshold average of <30 dB was observed in 76.5% in the ATF group and 63.1% in the underlay tympanoplasty group (P>0.05). The postoperative ABG of the ATF and underlay group patients were less than 20 dB in 76.5% and 78.9%, respectively (P>0.05). No graft lateralization, anterior blunting, or cholesteatoma were observed. Conclusion: ATF is a safe and effective technique with a higher success rate for repairing anterior tympanic membrane perforation.